Cortical visual impairment secondary to hypoglycemia - Kabakus, N; Yilmaz, T; Balci, TA; Kamisli, O; Kamisli, S; Yildirim, H (Taylor & Francis Ltd, 2005)
Cortical visual impairment (CVI) most commonly occurs in children after hypoxic insults but may also occur as a sequel of meningitis, encephalitis, head trauma, and hydrocephalus. CVI secondary to hypoglycemia is rarely encountered. A 4-year-old girl was admitted to hospital with a history of bilateral visual impairment. She had several severe hypoglycemic attacks lasting a week in the neonatal period. Bilateral occipital gliotic lesions were defined on magnetic resonance imaging (MR). [Tc-99m]-hexamethyl propylene a-mine oxime (HMPAO) brain single-photon emission computerized tomography (SPECT) was performed to determine the cerebral blood flow (CBF). SPECT images showed an extended hypoperfusion area in the right parieto-temporal region with marked non-perfusion areas in bilateral occipital cortices. It should be noted that hypoglycemia has devastating effects on cerebral tissues including optical areas and thus resulting in CVI. We would like to emphasize the importance of early diagnosis and prompt treatment.
Keywords: cortical visual impairment; hypoglycemia